Orthodontic treatment as a possible trigger of periodontal disease - Ann Lin (University Library System, University of Pittsburgh, 2016)
Background: Periodontal disease leads to the deterioration of oral health, including loss of teeth and its supporting structures. It has been established that the cause of this disease is multifactorial, indicating that both genes and environmental factors are intertwined with the formation and progression of periodontal disease. Case Description: Here we discuss the possibility of orthodontic treatment serving as a trigger to an early development of periodontal disease in a patient who has a family history of periodontitis. Between debonding at age 17.5 years and age 28, the patient experienced gradual general loss of attachment on the mandibular arch with the left mandibular canine having exaggerated attachment loss. Between age 28 and 29 years, the patient experienced exacerbated loss of attachment at both mandibular canines. Practical Implications: The occurrence of attachment loss during and after orthodontic treatment should not be overlooked. It is crucial for orthodontists to obtain a family history of periodontal disease and carefully monitor patient's periodontal conditions throughout the treatment.